Online customer relationship management: A systematic review and a future research agenda - Ziky, Rachid; Bahida, Hicham; Oulamine, Ayoub; Chakra, Raja; Massiki, Ayoub (International Journal of Innovative Research and Scientific Studies, 2025)
The rise of digital technologies, particularly social media, has profoundly reshaped customer relationship management (CRM), extending it beyond traditional frameworks to what is now referred to as online relationship management. This article presents a systematic review of the literature focused on empirical studies that examine the relationship between online relationship management and business performance in customer interactions. The main objective is to conduct a rigorous analysis of existing research, highlighting key contributions, identifying limitations, and proposing directions for future inquiry. To achieve this, we adopted the PRISMA methodology, which follows a structured four-step process for article selection and data analysis. Our findings reveal several gaps in the current literature, including the limited use of mixed-methods approaches, insufficient exploration of critical variables such as customer engagement, the predominance of small sample sizes, and a lack of research conducted across diverse geographical and cultural contexts. These insights offer a solid foundation for advancing theoretical development and guiding future empirical investigations in the field.